A Proposal for Designing a Novel Blockchain-Based Data Provisioning Mechanism for IoT Integration in Smart Applications - Al-Rammahi, Hussein; Asaad, Ameer Yalmaz (Peneliti Teknologi Teknik Indonesia, 2025)
The Internet of Things (IoT) presents unique communication and security challenges due to the diverse nature and sheer volume of connected devices. Traditional communication solutions are often insufficient to meet these demands. This paper addresses the critical need for robust security in IoT by proposing a novel, blockchain-based mechanism for secure data provision in smart applications. While security is frequently overlooked in IoT in favor of application and hardware development, distributed ledger technology (blockchain) offers a promising solution. Beyond its role in cryptocurrencies, blockchain offers inherent capabilities for device identity, secure data transfer, and immutable data storage, all within a decentralized and transparent system that provides auditable cryptographic proofs. This paper aims to thoroughly analyze blockchain technology and evaluate prominent frameworks such as Ethereum and Bitcoin. We will examine the distinct features and target use cases of these frameworks to determine the most suitable blockchain architecture for the IoT ecosystem. This paper provides a high-level comparison of the evaluated architectures, alongside sample use cases and ongoing research, to aid developers and managers in selecting an appropriate framework based on their specific application requirements. The core contribution is the design and initial validation of our novel mechanism, which enhances data integrity and trust within IoT environments.